2017
DOI: 10.1080/1061186x.2017.1315686
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin sensitizes prostate cancer cells to radiation partly via epigenetic activation of miR-143 and miR-143 mediated autophagy inhibition

Abstract: Curcumin has been reported as a radiosensitizer in prostate cancer. But the underlying mechanism is not well understood. In this study, we firstly assessed how curcumin affects the expression of miR-143/miR-145 cluster. Then, we investigated whether miR-143 is involved in regulation of radiosensitivity and its association with autophagy in prostate cancer cells. Our data showed that PC3, DU145 and LNCaP cells treated with curcumin had significantly restored miR-143 and miR-145 expression. Curcumin showed simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 36 publications
2
45
0
2
Order By: Relevance
“…At present, numerous evidences suggest that curcumin can also sensitize diverse types of malignant tumor to irradiation. 29,31,32 Curcumin is able to enhance the sensitivity of irradiation through inhibiting the expression of p53. 41 Curcumin sensitizes human colon cancer to radiation by affecting the levels of DNA repair-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…At present, numerous evidences suggest that curcumin can also sensitize diverse types of malignant tumor to irradiation. 29,31,32 Curcumin is able to enhance the sensitivity of irradiation through inhibiting the expression of p53. 41 Curcumin sensitizes human colon cancer to radiation by affecting the levels of DNA repair-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the role of miRNAs in the mechanisms involved in the protective effects of traditional Chinese medicine. For instance, Liu et al (37) revealed that curcumin can enhance sensitivity to radiation in prostate cancer cells via the regulation of miR-143. Moreover, Fan et al (38) demonstrated that emodin protects against hyperglycemia-induced injury in PC-12 cells via the upregulation of miR-9.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miRNAs are involved in autophagy in some cells including miR-106b, miR-124, miR-143, miR-155 and miR-375, etc. [ 8 , 10 , 12 , 16 , 23 ]. However, the role of miRNAs in the autophagy and apoptosis of CPCs under oxidative stress remains unclear.…”
Section: Introductionmentioning
confidence: 99%